Sports fishing in Malaysia have the time of your life : Pulau Redang - Epic Channel (Kuala Lumpur : Epic Channel [production company] ; VTR Distributors [distributor])
This episode brings to you first-hand information on new fishing spots, how the team won the'tug-of-war' with really un-friendly species while highlighting the natural beauty of Malaysia which surround us. The destination in this episode is Pulau Redang, an island located in the South China Sea, off the East Coast of Malaysia
Keywords: Fishing